Effective Circuit Configuration and Control for Coil-Array Wireless Power Transmitters - Hirokazu Matsumoto; Wataru Yoneyama; Aozora Hata; Yuki Sato (IEEE Open Journal of the Industrial Electronics Society, 2023)
This article presents a circuit configuration and control for coil-array wireless power transmitters. The target coil arrays have coils that are uniform in shape and dimensions and are regularly arranged with an angular interval of 120°. The system has a three-leg half-bridge inverter, which simultaneously feeds the three coils in the transmitter. It can deal with more than three coils by adding a switch set between the inverter and the coils. The system has a configuration to cancel mutual inductances between the transmitter coils and improve the power factor of the system. It can maximize the efficiency from the transmitter coils to the receiver coil and can output uniform power regardless of the receiver position. The current condition for achieving these features is derived, and a field-programmable-gate-array-based control for realizing the current condition is presented. The performance of the proposed system is experimentally validated with an implemented prototype. Results show that the system has a power variation of less than 5.8% depending on the receiver position. The system can operate at approximately maximum efficiency.